Junker's investment plan: What results can we expect? - Myant, Martin (Stockholm, 2015)
"There has been a fall in investments in several EU member states and the need to revive economic growth is often highlighted. Therefore, the European Commission has presented a plan for 315 billion euro of new investment. In this analysis, Martin Myant discusses this plan and finds that the investment supported is likely either to be much less than hoped or to be biased towards safer projects in higher income countries, increasing rather than reducing divergences across the EU. The plan could be improved by setting clearer objectives and criteria, increasing its scale and, above all, by allowing some relaxation of the strict budget rules applied within the eurozone."